Equation: 36711

Solve the equation:

5x- (6x + 9) = 10x + 2- (x + 5)

Please test the left and right sides. Thank you.

Correct answer:

x =  -0.6

Step-by-step explanation:

5 x(6 x+9)=10 x+2(x+5)  10x=6  x=106=0.6  x=53=0.6   Verifying Solution:  l=5 x(6 x+9)=5 (0.6)(6 (0.6)+9)=542=852=8.4 p=10 x+2(x+5)=10 (0.6)+2((0.6)+5)=542=852=8.4  l=p

Did you find an error or inaccuracy? Feel free to write us. Thank you!

Tips for related online calculators
Do you have a linear equation or system of equations and looking for its solution? Or do you have a quadratic equation?

You need to know the following knowledge to solve this word math problem:

Related math problems and questions: